Tahapan Pelaksanaan Program Bantuan Stimulan Perumahan Swadaya (BSPS) Sumatera Utara - Thirza Eunike Silaban; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
Poverty in Indonesia has resulted in many people who still have not achieved their welfare, one of which is in the fulfillment of habitable houses. In order to achieve community welfare through the fulfillment of habitable houses, the government through the Ministry of Public Works and Public Housing held a Self-Help Housing stimulant Assistance program for low-income communities, so as to improve the quality of people's homes to be habitable. To receive this program, there are several stages of implementation that need to be done, ranging from identification of potential beneficiaries to monitoring and evaluation reports. In the approach to the community of prospective beneficiaries, the method of community organization and community development is carried out by empowering the community with a direct approach as an approach to social work techniques that can be done to address the community or group of beneficiaries of macro programs. Several stages of intervention are Assessment, program Planning, Intervention, evaluation and termination stages. The focus of solving the problem is to empower the recipient group to be able to be empowered and independent in following the implementation of the BSPS program from the beginning to the end of the program. The purpose of this empowerment is also considered successful with the increasing enthusiasm of the recipient group community in completing the accountability for the implementation of the BSPS program and following the various stages of coordination and socialization of the BSPS program.